Chapter Migration and identity: thoughts on translation based on Yoko Tawada’s case - Vitali, Lelia (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
Taking as an example the emblematic case of the ‘exophonic’ writer Yoko Tawada, we will analyze some translation difficulties for the language pair German/Italian, which are due to linguistic differences and to topics related to the relationship between language and culture. In particular, we will examine two texts, originally written in German, for which an Italian translation has already been published. These works are Das Bad (1989) and Von der Muttersprache zur Sprachmutter (in Talisman, 1998) and focus thematically on personal and linguistic identity.